Parental Influence on Adolescents’ Knowledge and Attitudes Toward Early Marriage - Setya Wardani, Diadjeng; Rahayuningsih, Elba Putri; Rahmah, Shofi Nur (Sriwijaya Journal of Medicine, 2025)
East Java records the highest percentage of child marriage in Indonesia, at 10.44%, with Malang Regency ranking first with 1,455 marriage dispensations. Early marriage commonly occurs among adolescents who still need parental support. This study focuses on parental characteristics, including age, education, socioeconomic status, and sociocultural background. This study aimed to examine the relationship between parental characteristics and adolescents’ knowledge and attitudes regarding the dangers of early marriage. The study uses an analytical design with a cross-sectional approach, involving 43 students and 43 of their parents. Data are collected through questionnaires and analyzed using the Chi-Square test with a significance level of 0.05. There was no significant relationship between parents’ education, socioeconomic status, or sociocultural background and adolescents’ knowledge and attitudes. However, parents’ age showed a significant relationship with adolescents’ knowledge (p = 0.015) and attitudes (p = 0.012). The age of parents significantly affects adolescents’ knowledge and attitudes toward early marriage at SMPN 2 Singosari, Malang Regency.